1990
DOI: 10.1104/pp.94.4.1849
|View full text |Cite
|
Sign up to set email alerts
|

An Ethylene Biosynthesis-Inducing Endoxylanase Elicits Electrolyte Leakage and Necrosis in Nicotiana tabacum cv Xanthi Leaves

Abstract: We have previously demonstrated that a protein purified from xylan-induced culture filtrates of Trichoderma viride contains ,8-1,4-endoxylanase activity and induces ethylene biosynthesis in tobacco (Nkotiana tabacum cv Xanthi) leaf discs. When the ethylene biosynthesis-inducing xylanase (EIX) was applied to cut petioles of detached tobacco leaves, it induced ethylene biosynthesis within 1 hour and extensive electrolyte leakage and necrosis were observed in tobacco leaf tissue within 5 hours. Ethylenepretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
107
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 20 publications
0
107
0
Order By: Relevance
“…Several independent transgenic plants harboring the RNAi construct were generated, and antibiotic resistance and DNA gel blot analysis confirmed transformation ( Figure 4A). In responsive tobacco cultivars, EIX induces cell death within 48 h of treatment (Bailey et al, 1990) and complete tissue desiccation within 96 h. We examined the induction of cell death in 11 independent transgenic plants. Cell death by EIX was clearly suppressed compared with control plants ( Figure 4B).…”
Section: Silencing the Leeix Gene Family Abolishes The Response To Eimentioning
confidence: 99%
See 1 more Smart Citation
“…Several independent transgenic plants harboring the RNAi construct were generated, and antibiotic resistance and DNA gel blot analysis confirmed transformation ( Figure 4A). In responsive tobacco cultivars, EIX induces cell death within 48 h of treatment (Bailey et al, 1990) and complete tissue desiccation within 96 h. We examined the induction of cell death in 11 independent transgenic plants. Cell death by EIX was clearly suppressed compared with control plants ( Figure 4B).…”
Section: Silencing the Leeix Gene Family Abolishes The Response To Eimentioning
confidence: 99%
“…The 22-kD fungal protein ethylene-inducing xylanase (EIX; Fuchs et al, 1989) induces ethylene biosynthesis, electrolyte leakage, pathogensis-related protein expression, and HR in specific plant species and/or varieties (Bailey et al, 1990(Bailey et al, , 1993Ron et al, 2000;Elbaz et al, 2002). Analysis of EIX mutants lacking enzymatic activity (b-1-4-endoxylanase) but retaining elicitation activity showed that the xylanase activity is not required for the HR elicitation process because the protein per se functions as the elicitor (Enkerli et al, 1999;FurmanMatarasso et al, 1999;Rotblat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…pisi and Macrophomina phaseolina (8). Subsequent work has shown that the enzyme from T. viride also elicits other defense responses in tobacco, including synthesis of pathogenesisrelated proteins (18), tissue necrosis, and electrolyte leakage (3). Other fungal endoxylanases have been shown to elicit defense responses, such as phytoalexin production (10), lipid peroxidation (13), vascular gelling (29), and cell death (5), in various plant tissues.…”
mentioning
confidence: 99%
“…For determination of ethylene production, tobacco plants were dissected 20 min after EIX application by removing each leaf, leaving the petiole on the stem. Six 1-cm leaf discs were cut from the left and right sides of each leaf and bioassayed separately over a 4-h period for ethylene production as previously described (3,17). Ethylene biosynthesis-inducing activity is expressed as ,L ethylene evolved per h per g fresh weight of tobacco tissue.…”
Section: Symptom Measurementsmentioning
confidence: 99%
“…Immunoblots of proteins extracted from detached, EIX-treated leaves probed with EIX-specific antibodies demonstrated that EIX had moved into leaves from the point of application (3). In this report, the same EIX-specific antibodies have been used in conjunction with the technique of tissue printing (9) to examine the means by which EIX is transported in tobacco and how that transport leads to particular patterns of symptom development.…”
mentioning
confidence: 94%